ELT TEACHER STRATEGIES IN IMPLEMENTING CHARACTER EDUCATION (A Descriptive Study at SMP Negeri 5 Kalis in Academic Year 2020/2021) - hasri retno wanti; aunurrahman aunurrahman; sahrawi sahrawi; Elly Syahadati (XXXX-XXXX, 2022)
This qualitative research was conducted to analyze the teacher strategies in implementing character education in English learning. The subject of the research was active students at Eighth Grade and an English teacher of SMP Negeri 5 Kalis in the Academic Year of 2020/2021. The sample was selected using a purposeful sampling technique. The technique of data collection applied in this research were documentation, observation, and interview. Documentation was used to get data from the lesson plan. The observation was used to get data in the process of teaching and learning activities to know about the implementation of character education. Meanwhile, an interview was conducted with English teachers to get more information about teachers’ strategies in implementing character education. Based on the results of documentation, observations, and interviews, it can be concluded that the English teacher has implemented character education. The implementation strategies of character education that teachers use are role models, habits, assignments, discussions, cooperation, punishments, or rewards, as well as linking life values with the material being studied.